Optimization of Sales Order and Distribution in SAP with Profitability Reporting Option in Cloud Based SAAS applications - et. al., M. Usha Rani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this paper is to provide optimize ways in sales and distribution, marketing, product managementprocess. In order to sustain in this contemporary and dynamic environment, rapid and dynamic decision making is required to make right decision. In any organization profitability is the core parameter to assess while designing organization objectives, goals and strategies, profitability plays a major role to achieve them. This paper illustrates real time use cases of date integration using Fiori, migration and synchronization of data.